Implementação de padrões de tecimento na simulação de operações de soldagem pelo método dos elementos finitos - Pereira, Heitor Abdias da Silva (2019)
One of the most relevant factors for the appropriate behavior of a welded component when in service is its thermal history, given the high heat input involved in joining the parts as well as the defects related to the inadequate adjustment of the welding parameters. One of the most common practices to produce high-quality welds, with greater efficiency, is the execution of weaving movements during the process, because they provide a wider weld bead, the proper fusion of the joint edges, and other benefits. Although numerical methods, such as the Finite Element Method – FEM –, are widely used in the simulation of welding processes, the mathematical models of heat sources representing the electric arc action in the welded piece do not cover the weaving motion, and adaptations regarding the mathematical description of the heating during welding are therefore necessary. In this context, the present study proposes the incorporation of the weaving movement in welding simulation based on the parameterization of the path traveled by the heat source during the execution of the movement, with the establishment of two case studies, in which one establishes a comparison between the proposed method and the coordinate transformation method, the most commonly used technique, based on numerical and experimental data from the literature, as well as the realization of an experimental analysis to observe the thermal cycle in points of a welded plate. The results showed that, although it is a simpler method than the coordinate transformation one, the path parameterization is capable of accurately representing the weaving movement in welding simulations, thus providing relevant information regarding the temperature distribution and the thermal cycle of welding.